KECUKUPAN ENERGI DAN PROTEIN SERTA STATUS GIZI SISWA SMP YANG MENDAPAT MAKAN SIANG DAN TIDAK MENDAPAT MAKAN SIANG DARI SEKOLAH DENGAN SISTEM FULLDAY SCHOOL - Siti Nuraini Dongoran; Albiner Siagian; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
The teaching learning process activity of the school applied the fullday school system is conducted in full day (less than 9 hours). The student who study in this school has the higher learning activity than student in the public school. Therefore, the fullday school provide the student with or without lunch. This research aims to compare the energy and protein sufficiency and nutrition status of students of fullday junior high school. So it review whether the lunch provided by full day school satisfy the nutrition requirement of the students. This research was conducted at two fullday schools in Medan. Of each school the sample is 58 students. The anthropology data was collected by do the measurement of weight and height while the food intake data was collected by interview using recall form 24 hours for twice. The result of this research indicates the sufficiency of energy and nutrition status of the student in fullday school who get the lunch from school is better than student who did not obtain the lunch from school. While for protein sufficiency is contrary. But the lunch supplied by fullday school that provide the students with lunch did not fulfill the nutrition requirement of students. Therefore, the fullday school that provide the student with lunch and without lunch must consider the nutrition status of the student specially when student in the school. A good nutrition status will increase the body immune of student in order to preven any diseases for student and can learn effectively with the higher learning achievement. Keywords : energy sufficiency, protein sufficiency, nutritional status, lunch, junior high school student